Proliferation, Metastasis, and Radiosensitivity of Nasopharyngeal Carcinoma Cells in the Expression and Effect of Kiwifruit Extract through the Regulation of miR-205-5p. (11th August 2022) - Chen, Qiuqiu; Pan, Min; Lu, Yusong; Wei, Feifei; Chen, Chunqiao; Huang, Hui
Abstract : Background . Radix Actinidiae extract (RAE) has been shown to inhibit cancer in many studies, but its potential mechanism in nasopharyngeal cancer (NPC) progression remains unclear. Methods . NPC cells (SUNE1) were treated with different doses of RAE. For transfection, SUNE1 cells were transfected with the microRNA (miR)-205-5p inhibitor (anti-miR-205-5p) or mimic followed by treatment with 200 μ g/mL RAE for 24 h. The MTT assay and colony formation assay were used to detect cell proliferation and radiosensitivity. The transwell assay was used to detect cell migration and invasion. The expression of miR-205-5p was detected by quantitative real-time PCR. The protein expression levels of matrix metalloproteinase-2 (MMP2) and matrix metalloproteinase-9 (MMP9) were detected by western blot analysis. Results . RAE inhibited NPC cell proliferation, migration, and invasion, while it enhanced radiosensitivity (P < 0.05 ). Also, RAE treatment decreased miR-205-5p expression, as well as MMP2 and MMP9 protein levels (P < 0.05 ). Anti-miR-205-5p transfection enhanced the effects of RAE on NPC cell proliferation, migration, invasion, and radiosensitivity (P < 0.05 ), while miR-205-5p mimic transfection had an opposite effect (P < 0.05 ). Conclusion . RAE might decrease miR-205-5p, thereby it inhibited NPC cell proliferation and metastasis and enhanced radiosensitivity.